2015
DOI: 10.4162/nrp.2015.9.6.599
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion ofCitrus unshiupeel extracts with cytolase suppresses adipogenic activity in 3T3-L1 cells

Abstract: BACKGROUND/OBJECTIVESCitrus flavonoids have a variety of physiological properties such as anti-oxidant, anti-inflammation, anti-cancer, and anti-obesity. We investigated whether bioconversion of Citrus unshiu with cytolase (CU-C) ameliorates the anti-adipogenic effects by modulation of adipocyte differentiation and lipid metabolism in 3T3-L1 cells.MATERIALS/METHODSGlycoside forms of Citrus unshiu (CU) were converted into aglycoside forms with cytolase treatment. Cell viability of CU and CU-C was measured at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…HT is the aglycone form of hesperidin that is commonly present in citrus fruits. A few studies have reported that HT exhibits beneficial properties, including antioxidant, anti‐inflammation, and antiadipogenic activities (Bok et al, ; Lim et al, ; Yang et al, ; Ye, Chan, Chen, & Leung, ). Yang et al investigated the antioxidant and anti‐inflammatory effects of HT metabolites derived from HT‐administered rat serum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HT is the aglycone form of hesperidin that is commonly present in citrus fruits. A few studies have reported that HT exhibits beneficial properties, including antioxidant, anti‐inflammation, and antiadipogenic activities (Bok et al, ; Lim et al, ; Yang et al, ; Ye, Chan, Chen, & Leung, ). Yang et al investigated the antioxidant and anti‐inflammatory effects of HT metabolites derived from HT‐administered rat serum.…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid contents of CU include naringin, narirutin, and hesperidin, while CU‐C contains naringenin and hesperetin. The authors showed that CU and CU‐C suppressed three adipogenic transcription factors, including PPARγ, C/EBPα, and Sterol regulatory element‐binding protein‐1c (SREBP‐1c) in adipocyte differentiation (Lim et al, ). However, the effects of HT on lipid accumulation and ROS production as well as its molecular action during adipogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance of NK and CK was 0.39 and 0.27, respectively. Similarly, bioconversion of Citrus unshiu with cytolase (CU‐C) showed significant inhibitory effect on lipid accumulation at 0.5mg/ml (Lim et al, ). These results indicated that citrus concentrate inhibited lipid accumulation in 3T3‐L1 adipocytes, suggesting its antiobesity effect.…”
Section: Resultsmentioning
confidence: 99%
“…Such kind of natural immunostimulants are medicinal plants, among these C. limon , and citrus plants in general, have long been used to treat many diseases in traditional medicine such as obesity, diabetes, hypercholesterolaemia, high blood pressure, inflammation (Padilla‐Camberos et al, ; Park et al, ; Parra et al, ; Tort, ), brain disorders, cancer (Lim et al, ; Parra et al, ; Shetty et al, ; Tort, ), microbial infections (Ou et al, ; Park et al, ; Shetty et al, ), digestive disorders (Padilla‐Camberos et al, ; Park et al, ; Shetty et al, ), vitamin deficiencies (Shetty et al, ) and bronchial, asthmatic and degenerative diseases (Lim et al, ) among others. In general, the different parts of citrus plants have beneficial properties, for example immune‐enhancing (Padilla‐Camberos et al, ; Shetty et al, ) and anti‐toxic (Chowdhury et al, ), and present antioxidant (Cho et al, ; Gómez et al, ; Nouri & Shafaghatlonbar, ; Ou et al, ; Padilla‐Camberos et al, ; Wu et al, ), antibacterial (Ou et al, ; Ramadan et al, ; Shetty et al, ), anti‐diabetic (Menichini et al, ; Padilla‐Camberos et al, ; Wu et al, ), anti‐inflammatory (Ramadan et al, ), hepato‐protective (Chowdhury et al, ), neuro‐protective (Ramadan et al, ) and kidney‐protective (Sridharan et al, ) activities due to the phenolic compounds they contain, such as terpenes (Nakajima et al, ; Ou et al, ; Park, Lee, & Park, ; Park et al, ; Shetty et al, ) phenolic acids (Ou et al, ; Park et al, ; Shetty et al, ) and flavonoids (Gómez et al, ; Lee et al, ; Lim et al, ; Nakajima et al, ; Okuyama & Zasshi, ; Park et al, ; Shetty et al, ; Wu et al, ). For these important reasons it was decided to test the effects of this important fruit on gilthead seabream, as on...…”
Section: Discussionmentioning
confidence: 99%
“…Due to the negative impact of drugs and/or antibiotics on fish and human health, natural immunostimulants that enhance the immune system response are increasingly emerging as alternatives to prevent fish diseases (Bulfon et al, 2015; Van Hai, 2015;Harikrishnan et al, 2011;Mena et al, 2013;Reverter et al, 2014). Such kind of natural immunostimulants are medicinal plants, among these C. limon, and citrus plants in general, have long been used to treat many diseases in traditional medicine such as obesity, diabetes, hypercholesterolaemia, high blood pressure, inflammation (Padilla-Camberos et al, 2014;Park et al, 2016;Parra et al, 2015;Tort, 2011), brain disorders, cancer (Lim et al, 2015;Parra et al, 2015;Shetty et al, 2016;Tort, 2011), microbial infections (Ou et al, 2015;Park et al, 2016;Shetty et al, 2016) Furthermore, DLP was chosen because it is one of the main by-products of the lemon processing industry and we wanted to determine whether it could be incorporated in the fish diet without any previous treatment, acting as a nutraceutic additive, as realized for other farmed animals (Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%